2017
DOI: 10.1080/15384047.2017.1394549
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone exacerbates cytotoxic chemotherapy induced lethargy and weight loss in female tumor free mice

Abstract: Cytotoxic chemotherapy can induce a systemic inflammatory response which has been proposed to be an underlying mechanism of cancer treatment related fatigue. Dexamethasone, a synthetic glucocorticoid that has potent anti-inflammatory effects, is incorporated into chemotherapy regimens to prevent chemotherapy-induced nausea and vomiting (CINV). The purpose of this study was to determine whether by suppressing cytotoxic chemotherapy-induced inflammation, dexamethasone could ameliorate chemotherapy induced fatigu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…In cardioprotective studies, the administration of cyclophosphamide caused a significant body weight loss compared with the normal group. is effect was consistent with previous studies [45][46][47]. is might be due to anorexia as a result of the damaging effect of cyclophosphamide on the gastrointestinal tract or on the appetite center (ventromedial nucleus and lateral hypothalamus) in the hypothalamus [24,48].…”
Section: Discussionsupporting
confidence: 92%
“…In cardioprotective studies, the administration of cyclophosphamide caused a significant body weight loss compared with the normal group. is effect was consistent with previous studies [45][46][47]. is might be due to anorexia as a result of the damaging effect of cyclophosphamide on the gastrointestinal tract or on the appetite center (ventromedial nucleus and lateral hypothalamus) in the hypothalamus [24,48].…”
Section: Discussionsupporting
confidence: 92%
“…When evaluating fatigue-like behavior, investigators may find “time active” to be the more stable measure on a daily basis, particularly when looking at 1-minute intervals like we did. This idea may be supported by recent results testing chemotherapy-related fatigue, in which the time on the running wheel may appear to be more stable 14 , though calculated wheel time using 1-hour intervals. However, another study looking at post-exercise fatigue did not appear to find much difference between the two measures 21 .…”
Section: Discussionmentioning
confidence: 77%
“…In clinical studies, fatigue is typically determined by self-reports and questionnaires, and rarely using behavioral or physical measurements 2 . In contrast, with preclinical mouse models investigators have published quite a few behavioral measures of physical activity to measure fatigue, including: running wheels 7 9 , 11 , 12 , 14 – 17 , 20 , 21 ; home cage monitoring using video 7 , 8 , 18 , telemetry 11 , or cages with light beams/sensors 20 ; treadmills 10 , 19 , 21 ; forced swim 8 , 9 ; and open field 12 . However, there are no standards for which methods should be considered reliable indicators of fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that Dex can inhibit the proliferation of a variety of cancer cell lines ( 29 , 30 ). Dex also inhibits the proliferation of Chinese hamster ovary cells, HeLa S3 cervical cancer cells, and the human ovarian cancer cell line 3AO ( 8 ).…”
Section: Discussionmentioning
confidence: 99%